Stages to set up a company with a minimal investment in Guayaquil - ESPOL (2011)
This project describes the stages to go through in setting up a micro-company with a minimal investment, which is the priority when we think in making a company, doing it is not easy, this is a careful planned process since the name, place until the launch a micro-company and make a follow up to be a success. We will analyze step by step to apply it.